Numbers and the Church: Statistical Surveys of Christian Churches in Modern China - ZHOU, Yuqian (Journal of Research for Christianity in China (JRCC), 2025)
Numbers provide us with the potential and space for imagination; through them, we gain the possibility of grasping the external world. Traditional China did not emphasize precise numerical data, and thus lacked quantitative management. However, missionaries with Western backgrounds who came to China to spread the faith deeply integrated their survey and statistical methods into missionary work, significantly influencing contemporary missionary activities. The series of surveys and statistics they left behind have become indispensable materials for subsequent research on Christianity. Therefore, this paper will trace and examine the series of statistical surveys conducted during the development of Christianity in modern China from a historical perspective. Given that Protestantism left extensive records in this area, the focus will be on the large-scale statistical activities undertaken by Protestant groups. We will explore how they conducted surveys of the loosely organized Protestant churches at the time, what data they obtained, and how this data served their own governance.
Keywords: Survey Statistics; The Chinese Recorder; Chinese Continuation Commission Office